Work Motivation, Work Environment, and Job Satisfaction as Drivers of Employee Performance: Motivasi Kerja, Lingkungan Kerja, dan Kepuasan Kerja sebagai Faktor Pendorong Kinerja Karyawan - Susanti, Wahyu Sukma Dewi; Prapanca, Detak (Indonesian Journal of Law and Economics Review, 2024)
General Background: Employee performance plays a crucial role in supporting productivity within the mini-cigar industry. Specific Background: PR. Tri Putra Sentosa faces challenges related to work conditions, employee motivation, and satisfaction, which may influence overall performance. Knowledge Gap: Previous studies show inconsistent findings regarding the roles of motivation, work environment, and job satisfaction, indicating the need for further examination in different organizational contexts. Aim: This study aims to analyze how work motivation, work environment, and job satisfaction contribute to employee performance at PR. Tri Putra Sentosa. Methods: A quantitative design was used with 110 employees selected through total sampling. Data were collected via Likert-scale questionnaires and analyzed with classical assumption tests, multiple regression, t-tests, and F-tests. Results: All three variables significantly contribute to employee performance, both individually and simultaneously, with the work environment emerging as the strongest predictor. Novelty: This study offers new insights by examining these variables using a larger sample size within the mini-cigar manufacturing context. Implications: The findings highlight the importance of improving workplace conditions and fostering supportive organizational practices to enhance employee performance. Highlights:• Largest predictor is work environment• Motivation and satisfaction consistently support performance• Practical relevance for labor-intensive industries Keywords: Work Motivation, Work Environment, Job Satisfaction, Employee Performance, Manufacturing